Activation of the Catalytic Activity of Thrombin for Fibrin Formation by Ultrasound. Issue 26 (19th May 2021) - Zhao, Pengkun; Huo, Shuaidong; Fan, Jilin; Chen, Junlin; Kiessling, Fabian; Boersma, Arnold J.; Göstl, Robert; Herrmann, Andreas
Abstract: The regulation of enzyme activity is a method to control biological function. We report two systems enabling the ultrasound‐induced activation of thrombin, which is vital for secondary hemostasis. First, we designed polyaptamers, which can specifically bind to thrombin, inhibiting its catalytic activity. With ultrasound generating inertial cavitation and therapeutic medical focused ultrasound, the interactions between polyaptamer and enzyme are cleaved, restoring the activity to catalyze the conversion of fibrinogen into fibrin. Second, we used split aptamers conjugated to the surface of gold nanoparticles (AuNPs). In the presence of thrombin, these assemble into an aptamer tertiary structure, induce AuNP aggregation, and deactivate the enzyme. By ultrasonication, the AuNP aggregates reversibly disassemble releasing and activating the enzyme. We envision that this approach will be a blueprint to control the function of other proteins by mechanical stimuli in the sonogenetics field. Abstract : The precise regulation of protein activity is important to understand complex biological signaling networks and to devise new therapeutic approaches. Here, we use either polyaptamers or split aptamer‐conjugated AuNPs to inhibit the activity of thrombin. Mechanical force generated by ultrasound is exploited to activate thrombin, thereby catalyzing the formation of fibrin from fibrinogen.